The impact of tomato fruits containing multi-walled carbon nanotube residues on human intestinal epithelial cell barrier function and intestinal microbiome composition. Issue 8 (11th February 2019) - Lahiani, Mohamed H.; Khare, Sangeeta; Cerniglia, Carl E.; Boy, Ramiz; Ivanov, Ilia N.; Khodakovskaya, Mariya
Abstract : Residues of Carbon Nanotubes in tomato fruits are too low to show significant impact on epithelial cell barrier and microbiome composition. Abstract : Carbon nanomaterials (CNMs) can positively regulate seed germination and enhance plant growth. However, clarification of the impact of plant organs containing absorbed CNMs on animal and human health is a critical step of risk assessment for new nano–agro-technology. In this study, we have taken a comprehensive approach to studying the effect tomato fruits derived from plants exposed to multi-walled carbon nanotubes (CNTs) have on gastrointestinal epithelial barrier integrity and their impact on the human commensal intestinal microbiota using an in vitro cell culture and batch human fecal suspension models. The effects of CNTs on selected pure cultures of Salmonella enterica Typhimurium and Lactobacillus acidophilus were also evaluated. This study demonstrated that CNT-containing fruits or the corresponding residual level of pure CNTs (0.001 μg ml −1 ) was not sufficient to initiate a significant change in transepithelial resistance and on gene expression of the model T-84 human intestinal epithelial cells. However, at 10 μg ml −1 concentration CNTs were able to penetrate the cell membrane and change the gene expression profile of exposed cells. Moreover, extracts from CNT-containing fruits had minimal to no effect on human intestinal microbiota as revealed by culture-based analysis and 16S rRNA sequencing.